2019
DOI: 10.1108/jqme-01-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic algorithm for optimal redundancy allocation in complex systems

Abstract: Purpose The purpose of this paper is to present an efficient heuristic algorithm based on the 3-neighborhood approach. In this paper, search is made from sides of both feasible and infeasible regions to find near-optimal solutions. Design/methodology/approach The algorithm performs a series of selection and exchange operations in 3-neighborhood to see whether this exchange yields still an improved feasible solution or converges to a near-optimal solution in which case the algorithm stops. Findings The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Now consider 5 unit Bridge system for nonlinear constraints as in Example 1 of Aggarwal. 30 Table 3 shows the procedure to obtain the optimal solution.…”
Section: Constrained Redundancy Optimizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Now consider 5 unit Bridge system for nonlinear constraints as in Example 1 of Aggarwal. 30 Table 3 shows the procedure to obtain the optimal solution.…”
Section: Constrained Redundancy Optimizationmentioning
confidence: 99%
“…Agarwal and Aggarwal 16 showed that their algorithms perform better than those in Kohda and Inoue and Shi 18,19 and provide attractive alternatives to that of Kim and Yum. 20 Recently, Aggarwal 30 proposed a heuristic algorithm based on 3-neighborhood, which is an improvement over Agarwal et al 25…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations